A novel hybrid differential evolution and symbiotic organisms search algorithm for size and shape optimization of truss structures under multiple frequency constraints. (1st December 2021) - Nguyen-Van, Sy; Nguyen, Khoa T.; Luong, Van Hai; Lee, Seunghye; Lieu, Qui X.
Abstract: Although a large number of metaheuristic algorithms and their variants have been proposed for many engineering optimization problems, no paradigms hybridized by differential evolution (DE) and symbiotic organisms search (SOS) to concurrently improve the optimal solution quality and the convergence speed have been published thus far, especially for size and shape optimization of truss structures with multiple frequency constraints. Therefore, this article aims to propose a novel optimization algorithm as a cross-breed of the DE and the SOS, named HDS, for such problems. This algorithm can simultaneously and effectively enhance both global and local searching abilities by utilizing newly developed operators hybridized from the DE and SOS. An automatically adapted parameter is suggested for a better trade-off between those two capabilities. Furthermore, an elitist scheme is used in the selection phase to extract the best solutions for the next generation. As a consequence, the proposed methodology results in high-quality optimal solutions with a lower computational effort in comparison with two original methods, even many other optimization paradigms available in the literature. 26 benchmark mathematical functions are examined first. 5 numerical examples of shape and size optimization of truss structures are then investigated to validate the feasibility of the current paradigm. Highlights: A novel hybrid differential evolution and symbiotic organisms search (HDS) is suggested. This HDS is crossbred between differential evolution (DE) and symbiotic organisms search (SOS). The HDS yields high-quality optimal solutions with a lower computational effort. 26 mathematical functions along with 5 examples of shape and size truss optimization are tested.